Critical hate studies: A new perspective - James, Zoë (International review of victimology, 2022)
This paper sets out a critical perspective that cohesively explains why hate happens in late modernity and its impact on the lived experience of victims. The paper challenges existing theoretical accounts of hate by presenting a psycho-social approach to subjectivity that acknowledges the impact of neoliberal capitalism on the lived experience. By doing so, the paper is able to account for the extremities of hate in society and its apparent normalcy. In conclusion, the paper argues that an interrogation of the extent of the harms of hate should be framed within a positive discourse wherein the human need to flourish, rather than survive, is recognised.